Pengaruh Penempatan Pegawai Terhadap Kinerja Pada Dinas Perhubungan Kota Denpasar Tahun 2016 - Ratnawati, Ni Luh Tut Tri; Pascarani, Ni Nyoman Dewi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRACT Civil servant which required placement effectively . Employee placement must be applied selectively according to the right position to be able to bring the agency on the expected performance result . But the organization structure in the Departement Of Transportation Denpasar did not correspond to current needs. This type of research is a quantitative research. Population studied are the civil servant in the Department Of Transportation Denpasar with the amount to 154 people . The sample in this study was 61 people by using simple random sampling technique. The results showed that employee placement positive and significant impact on performance, with the regression equation Y = 23.037 + 0.540 X. Result of R Square meaning that of 46.7% performance variation effected by variations in employee placement, while the remaining 53.3% explained by other factors. Keyword: Employee Placement, Performance, Departement Of Transportation Denpasar